Proceedings of the Fourth International Joint Conference on Autonomous Agents and Multiagent Systems 2005
DOI: 10.1145/1082473.1082615
|View full text |Cite
|
Sign up to set email alerts
|

Catch me if you can

Abstract: Embodied conversational agents become more and more realistic concerning their conversational and their nonverbal behaviors. But if the information conveyed nonverbally exhibits clues that are not consistent with the verbal part of an agent's action, how will the user react to such a discrepancy? Masking ones real emotions with a smile is a naturally occuring example of such a discrepancy. But such masks are often deficient and thus subtle clues of lying and deceiving manifest themselves in facial expressions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For example, in a game that allowed competition and cooperation (Prisoner’s Dilemma, Pruitt & Kimmel, 1977), a virtual human who smiled after making a competitive move evoked more competitive and less cooperative responses from human participants compared with a virtual human using an identical strategy in the game (tit-for-tat) but who smiled after cooperating. Virtual humans who make a verbal comment about a film that is inconsistent with their facial movements, such as saying they enjoyed the film but grimacing, quickly followed by a smile, were perceived as less reliable, trustworthy, and credible (Rehm & Andre, 2005).…”
Section: Perceiving Emotions From Facial Movements: a Review Of The Smentioning
confidence: 99%
“…For example, in a game that allowed competition and cooperation (Prisoner’s Dilemma, Pruitt & Kimmel, 1977), a virtual human who smiled after making a competitive move evoked more competitive and less cooperative responses from human participants compared with a virtual human using an identical strategy in the game (tit-for-tat) but who smiled after cooperating. Virtual humans who make a verbal comment about a film that is inconsistent with their facial movements, such as saying they enjoyed the film but grimacing, quickly followed by a smile, were perceived as less reliable, trustworthy, and credible (Rehm & Andre, 2005).…”
Section: Perceiving Emotions From Facial Movements: a Review Of The Smentioning
confidence: 99%
“…Focusing on conveying more subtle and complex emotional expressions, Rehm and André (Rehm & André, 2005) implemented some "fake expressions" (modifying subtly the real expression combining it with an opposite emotion) with the objective of portraying a character who was lying to the users. Their experiments showed that that participants were able to notice the differences between genuine and faked smiles.…”
Section: Related Workmentioning
confidence: 99%